Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kritis Ditinjau Dari Kecerdasan Interpersonal Siswa - Pakpahan, Gesti Marsaulina Br.; Aziz, Tian Abdul; Ambarwati, Lukita (Cetta: Jurnal Ilmu Pendidikan, 2025)
Students’ critical thinking skills are still relatively low, despite the importance of these skills in facing the challenges of the 21st century. This study aims to explore the effect of the Problem-Based Learning (PBL) model on enhancing students’ critical thinking skills, considering the level of interpersonal intelligence. The research uses a posttest-only treatment by level (2 x 2) design, with the dependent variable being critical thinking skills, and the independent variables including the learning model (PBL and conventional) and interpersonal intelligence (high and low). The sample consists of 144 eighth-grade students from two public junior high schools in West Jakarta, selected using cluster random sampling technique. The results show that students taught with the PBL model exhibited better critical thinking skills than those taught with the conventional model. Furthermore, students with high interpersonal intelligence demonstrated superior critical thinking skills compared to those with low interpersonal intelligence. The study also identifies a significant interaction between the learning model and interpersonal intelligence, where students with high interpersonal intelligence who received PBL instruction showed the best critical thinking outcomes. In conclusion, the PBL model has been proven to significantly improve critical thinking skills, especially in students with high interpersonal intelligence. These findings provide guidance for educators to consider students’ characteristics when selecting the appropriate teaching model to support the development of their critical thinking skills.